URUSOVITE, CU[ALASO5], A NEW MINERAL FROM THE TOLBACHIK VOLCANO, KAMCHATKA, RUSSIA - Vergasova L.P.; Filatov S.K.; Gorskaya M.G.; Molchanov A.A.; Krivovichev S.V.; Ananiev V.V. (My University, 2000)
Urusovite, ideally Cu[AlAsO5], has been found in a fumarole in the North Breach of the great fissure Tolbachik eruption (1975-76, Kamchatka peninsula, Russia). It occurs as light-green plates up to 0.4 mm in maximal dimension, tabular on {100}, elongated along [001]; well-developed forms are {100}, {010}, {110}, {011}, {111}. Associated minerals are: ponomarevite, piypite, sylvite, dolerophanite, euchlorine, tenorite, hematite and two unknown As-bearing minerals. Urosovite is brittle and has a perfect cleavage on (100), a vitreous luster and a white streak. H = 378 kg/mm2. Biaxial, optically negative, α = 1.672(2), β = 1.718(2), γ = 1.722(2), 2V(meas) ~ 30(2)°, 2V(calc) = 32.2°. Optical orientation is b = β, c - α. Pleochroism is in the light-green tones: α - colourless, β - light-green, γ - light-green. The mineral is monoclinic, space group P21/c, a = 7.134(2), b = 10.223(3),c = 5.576(2) Å, β = 99.79(3)°, V = 410.9(2) Å3. The diagnostic lines of the X-ray powder diffraction pattern are (I-d-hkl): 100-7.20-100; 9-4.844-011; 23-4.327-1̄11; 10-3.604-200; 10-3.174-121; 20-3.125-211; 6-2.656-012; 8-2.458-221. Urusovite is isostructural with Fe2+[AlPO5]. Microprobe analysis gave the following chemical composition (wt. %): CuO 32.23 (30.97-32.82), Al2O3 20.89 (20.44-21.44), Fe2O3 0.32 (0.10-0.72), ZnO 0.25 (0.10-0.43), As2O5 46.02 (44.97-47.17), V2O5 0.12 (0.00-0.40), Σ 99.83 (98.71-100.64). The empirical formula of urusovite, (Cu0.99Zn0.01)(Σ1.00)Al1.00As0.98O5.00, calculated on the basis of 5 O atoms, is close to the ideal one, Cu[AlAsO5], confirmed by crystal-structure analysis. The mineral is named urusovite in honour of Vadim Sergeevich Urusov (1936-), crystal chemist, Corresponding Member of the Russian Academy of Sciences, chair of the Department of Crystallography and Crystal Chemistry of Moscow State University.